The Effect of Whatsapp Broadcast Media Education on Adolescents' Knowledge about Dental and Oral Health for Gingivitis Prevention - Maya Ulpa; William Arisandi; Armen Patria (Universitas Ibn Khaldun Bogor, 2026)
Dental The high prevalence of gingivitis among adolescents is influenced by limited health promotion at Puskesmas Labuhan Ratu, resulting in low knowledge of gingivitis prevention among adolescents. This study provides health education through Broadcast WhatsApp to improve adolescents’ knowledge. The intervention is expected to serve as an innovative model for health promotion at the Puskesmas and to reduce the risk of gingivitis among adolescents. At Puskesmas Labuhan Ratu, 55 cases of gingivitis were reported among adolescents from January to May 2025. This study aims to determine the effect of health education via Broadcast WhatsApp on increasing adolescents’ knowledge of gingivitis prevention. This research is a quantitative study using a pre-experimental design with a one-group pretest-posttest approach. The study was conducted on July 10–20, 2025, in the working area of Labuhan Ratu Community Health Center. The population consisted of adolescents aged 14–18 years, with a Quota sampling of 40 participants selected using purposive sampling. The data collection instrument was a Google Form questionnaire distributed before and after the WhatsApp Broadcast educational intervention. Univariate analysis results showed an increase in the average knowledge score from 11.45 to 17.08. Bivariate analysis using the Paired Sample T-Test showed a p-value of 0.001 (p < 0.05), indicating a significant effect between before and after the WhatsApp Broadcast education. The findings show that health education via Broadcast WhatsApp is effective in improving adolescents’ knowledge of gingivitis prevention. Broadcast WhatsApp can serve as an effective digital strategy in health promotion programs, particularly to enhance knowledge and preventive behaviors regarding gingivitis among adolescents.